Perceptions of industry and education practitioners regarding 21st-century multiple intelligence qualifications for vocational education - Johan, Arif Bintoro; Mutohhari, Farid; Hadi, Samsul; Rabiman, Rabiman; Widodo, Widodo; Khaharsyah, Alfat (Faculty of Engineering, Universitas Negeri Yogyakarta, 2024)
Work development in the 21st century requires new multiple intelligence qualifications for vocational education (VE) to face it. This research reveals a new multiple intelligence qualification along with its application procedures and assessment aspects for VE. Industry practitioners and higher vocational education were involved in exploring data related to the topic in this research. Data collection on practitioners was carried out in two stages, starting with interviews and continuing with Focus Group Discussions. The transcribed data was then explained and interpreted using NVivo 12 plus. Four multiple intelligences are essential to industry practitioners and higher vocational education, namely interpersonal, intrapersonal, logistical, and naturalistic intelligence. Building these four multiple intelligences requires infrastructure support that is dominated by digital infrastructure, emphasis on the role of responsibility for the subjects involved in learning, increasing the readiness of teachers and students before learning, and determining learning strategies to encourage independence in students to explore in depth about what should be done achieved. These new intelligences are assessed based on three main aspects: self-assessment methods, peer assessment and meaningful project assessment. These findings are essential recommendations for education and learning administrators in VE to implement the four new multiple intelligences optimally and according to current work needs